Excellence fulfilled? On the unique developmental needs of professional athletes - Baker, Joseph; Johnston, Kathryn; Singh, Harjiv; Farah, Lou; Lablans, Dale (Frontiers in Sports and Active Living, 2023)
While the term ‘athlete development’ has been used to capture the changes (physical, psychological, etc.) that occur as an athlete moves from initial sport engagement to elite performance, much of the research in this area has focused on earlier stages of the pathway, with very little work examining the highest levels of sport. Considering a person’s bio-psycho-social development continues through adulthood, the limited attention to development for athletes at higher competitive levels is perhaps surprising. In this short article, we highlight several notable discrepancies between different competitive levels (e.g., pre-professional sport and professional sport) in the way development is conceptualized, contextualized, and operationalized. We use available evidence to provide guidance for researchers and practitioners to encourage the delivery of structured developmental programming in professional sport systems to aid with the transitionary period between pre-elite and elite levels, and to help foster career longevity.